"It turned my life upside down": the experience of Polish caregivers of siblings with Alzheimer's disease. Issue 9 (2nd September 2019) - Leszko, Magdalena
ABSTRACT: The aging of the population and the increased rate of individuals with Alzheimer's disease represents an increased challenge not only for older adults but also their caregivers. Sibling caregivers face multiple challenges associated with their role. Caring for individuals with Alzheimer's poses a significant burden and is associated with increased caregiver mortality, depression, mental and physical fatigue, lethargy and financial upheaval. The purpose of this qualitative study was to explore the experiences of sibling caregivers of Alzheimer's patients living in Poland. Semi-structured interviews were conducted with eleven siblings, primary caregivers of individuals with Alzheimer's disease. Four themes were identified: (a) role overload; (b) emotional impact, (c) changes in the relationship, and (d) fears about the future. Sibling caregivers experience challenges related to care recipients' behavioral problems as well as fatigue in having to be diligent and perform multiple care roles. The findings also revealed the impact of the disease disclosure on the relationship between caregivers and their sibling care recipient. The results from this study offer important implications for future interventions that could benefit individuals with Alzheimer's disease, their sibling caregivers, and the formal social support system in Poland.